Prevalence of Cross Bite Among the Orthodontic Patients in Bangabandhu Sheikh Mujib Medical University - Sultana, Naznin; Hassan, Gazi Shamim; Jha, Digamber; Nashrin, Towhida; Nahar, Lutfun; Naim, Mir Abu (Bangladesh Journal of Medicine, 2015)
Crossbite is one of the most prevalent malocclusion, posterior crossbite occurs in 8% to 22% of orthodontic cases and anterior crossbite has been seen in Class III cases, which accounts for 3.4% of orthodontic cases. The etiology of posterior crossbite can include any combination of dental, skeletal, and neuro muscular functional components, but the most frequent cause is reduction in width of the maxillary dental arch. Patients/cases seeking comprehensive orthodontic treatment in between 5 to 35 years were diagnosed for crossbite with diagnostic model and care record file. Out of 300 cases 163(54.3%) had crossbite, 90(30%) had anterior crossbite and 109(36.3%) had posterior cross bite. Among posterior crossbite 60(20%) had unilateral and 49(16.3%) had bilateral crossbite. Posterior crossbite was more prevalent than anterior crossbite. Cases with Class I molar relation showed more crossbite. Crossbite was more prevalent in cases with congenitally missing teeth. Bangladesh J Medicine Jan 2015; 26 (1) : 9-12